Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Unit Delivery Service PT PAM Lyonnaise Jaya Cabang Kebon Jeruk, Jakarta Barat Periode Juli – Desember Tahun 2022 - Damanik, Krisman; Sidjabat, Sonya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study examines the impact of service quality and level of consumer satisfaction on customer loyalty at PT PAM Lyonnaise Jaya, which operates as a clean water provider for West Jakarta. The researcher applied a descriptive methodology with multiple regression analysis techniques, where the main data collection was carried out by distributing questionnaires to 60 respondents. The results of the analysis revealed that there was a positive influence of the service quality variable on consumer loyalty with a value of 0.126, while the customer satisfaction variable showed a more significant impact with a value of 0.167. When these two variables were tested simultaneously, it was found that they contributed 64.4% to the formation of customer loyalty, while the other 36% was influenced by variables outside the research. Based on these findings, it can be concluded that improving aspects of service quality and customer satisfaction has a real impact in building consumer loyalty. Thus, it is recommended that company management pay special attention to the development of these two aspects as a strategy to maintain and increase customer loyalty